Impact of hemophilia on school, work, and leisure activities of patients assisted at the Hemocentro Regional de Montes Claros/Minas Gerais (Research, Society and Development, 2022)
Hemophilias are bleeding diseases determined by the deficiency of coagulation factor VIII (hemophilia A) or factor IX (hemophilia B). This study aimed to analyze the impact of hemophilia on the school, work, and leisure activities of patients seen at the Hemocentro Regional de Montes Claros/MG. This is a cross-sectional, descriptive, quanti-qualitative study, based on interviews and data from medical records. The data were submitted for statistical analysis. Participated in the research 22/43 male subjects, over 18 years old, with hemophilia. Age ranged from 20 to 54 years. The majority (10/22) presented the moderate form and 4/22 the severe form. One participant had a high-titer inhibitor. There was a prevalence of incomplete high school education (5/22), paid activity (12/22), and retired (8/22). The reported income was 1 minimum wage for 40.9%. The main complications recorded were hemarthrosis (17/22), mainly in the knees and elbows. In the group, 40.9% perform regular physical activity and the most frequent leisure activities were watching movies, TV, computer, and online games. Most were single (68.2%) and those who had children corresponded to 36.4%. Discussion: Hemorrhagic events in hemophilia worsen the quality of life. In this study, 36.4% participate in the secondary/ tertiary prophylaxis program with factor VIII or IX. Early initiation of primary prophylaxis (Ministry of Health, 2015) and patient compliance, allow promising results, particularly in reducing degenerative arthropathies, often disabling (Bezerra, 2022). It is concluded that hemophilia interferes with school, work, and leisure activities, and prophylaxis programs, DDU, and access to multiprofessional care are determinants for a better quality of life for these patients.